Extracranial-intracranial bypass surgery for intracranial aneurysm of the anterior cerebral circulation: A systematic review and meta-analysis - Chen, Yang; Chen, Pengyu; Duan, Guosheng; Li, Ren; Li, Ziao; Guo, Geng (Frontiers in Neurology, 2023)
Background: The safety of extracranial-intracranial (EC-IC) bypass in the management of anterior circulation intracranial aneurysms (IAs) remains to be determined. This systematic review aims to summarize the existing evidence and provide guidance for the precise management of IAs. Data source: We constructed search strategies and comprehensively searched Pubmed, Medline, Embase, Web of science, and Cochrane library. Methods: This systematic review was actualized according to the PRISMA statement. We evaluated study quality using the methodological index for non-randomized study (MINORS). Effect sizes were pooled using a random-effects model. Heterogeneity between studies was assessed using the I2 test. Publication bias was assessed using the Egger’s test. The registration number for this systematic review is CRD42023396730. Result: This systematic review included a total of 21 articles, involving 915 patients. Postoperative bypass patency rate was 99% (95% CI 0.98-1.00); short-term follow-up was 98% (95% CI 0.94-1.00); long-term follow-up was 95% (95% CI 0.93-0.97). The long-term follow-up rate of saphenous vein was higher than that of radial artery (OR 6.10 95% CI 1.04-35.59). Short-term surgery-related mortality was 0.3% (95% CI 0.000-0.012); long-term follow-up was 0.4% (95% CI 0.000-0.013); The proportion of patients with a score of 0-2 on the modified Rankin Scale (mRS) during long-term follow-up was 92% (95% CI 0.86-0.98). The incidence rates of long-term follow-up complications were: ischemic 3% (95% CI 0.01-0.06); hemorrhagic 1% (95% CI 0.00-0.03); neurological deficit 1% (95% CI 0.00-0.03); other 3% (95% CI 0.01-0.06). Limitation: Most of the included studies were retrospective studies. Studies reporting preoperative status were not sufficient to demonstrate postoperative improvement. Lack of sufficient subgroup information such as aneurysm rupture status. Conclusion: EC-IC therapy for anterior circulation IAs has a high safety profile. Higher level of evidence is still needed to support clinical decision.